Hydrogen Permeation Behavior of Carbon Steel During Corrosion in Highly Pressed Saturated Bentonite - Zhang, Qichao; Jiang, Yishan; Zhao, Xin; Song, Penglei; Kuang, Tingting; Chen, Juna; Sun, Zhongtao; Zhang, Yaopeng; Ai, Xiayu; Lu, Dongzhu; Huang, Yanliang (Frontiers in Materials, 2022)
Deep geological disposal is the most reliable method for high-level nuclear waste (HLNW), of which metal container as the first barrier for deep geological disposal of HLNW is particularly important. Carbon steel is used as container material because of the low possibility of local corrosion in bentonite. However, after the storage is closed, the decrease of oxygen content will create the the near-field environment where the hydrogen embrittlement(HE) in corrosion process of container could happen. In order to evaluate the safety of container in deep geological disposal of Beshai, the preselected area in China, hydrogen permeation efficiency(HPE) and HE were estimated in highly pressed saturated bentonite by electrochemical and extrapolation analysis. It is concluded that HPE increases with the disposal year, which proves that the hydrogen evolution reaction dominates the cathode process in the corrosion during long-term disposal. However, slow strain rate tensile (SSRT) shows the Q235 steel has a low HE sensitivity.